DEVELOPING JAM DORAEMON BERMAIN (JOIN) INSTRUCTIONAL MEDIA FOR THIRD GRADERS OF ELEMENTARY SCHOOL - Rizky Maulidia; Endang Poerwanti; Nawang Sulistyani (Pascasarjana UM, 2022)
Educational media plays a pivotal role and forms an essential component within the educational framework. For third-grade students in elementary schools or madrasahs studying the theme of energy transformation and its sub-theme of energy sources, pedagogical tools are necessary for teachers to effectively impart thematic content, particularly in relation to the concept of time (hours). The methodological approach employed in this study is structured around the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The study's objectives were twofold: (1) To understand the development of the JOIN medium in relation to the sixth theme, first sub-theme, for third grade elementary/madrasah students, and (2) To gauge the degree of student engagement with the JOIN medium. The participants of the study comprised 17 third-grade students from Madrasah Mambaul Ulum Malang in the 2018/2019 academic year. The research yielded two key findings. Firstly, the JOIN tool, a large craft resembling the Japanese character Doraemon with an analogue clock integrated into its design and a pouch for storing thematic materials and questions, serves as a thematic learning medium, facilitating teachers in the transmission of educational content. Secondly, the study revealed a high level of student enthusiasm and enjoyment with the JOIN tool during the learning process. A questionnaire was employed to measure the students' reaction, revealing a very high validity rating of 92%. The teachers' response was similarly high at 90%, while content experts rated the tool at 84%. Initially, the tool expert gave an assessment of 88%, which increased to 97% following revisions. The study therefore concludes that the JOIN tool demonstrates high validity and is thus deemed an effective supplementary resource for the teaching and learning process.